Acute metabolic responses after continuous or interval exercise in post‐menopausal women with overweight or obesity. (18th September 2020) - Dupuit, Marine; Boscaro, Audrey; Bonnet, Alban; Bouillon, Patrice; Bruno, Pereira; Morel, Claire; Rance, Mélanie; Boisseau, Nathalie
Abstract : This pilot study compared the effects of acute high‐intensity intermittent exercise (HIIE) and moderate‐intensity continuous exercise (MICE) on post‐exercise VO2, fat utilization, and 24‐hours energy balance to understand the mechanism of higher fat mass reduction observed after high‐intensity interval training in post‐menopausal women with overweight/obesity. 12 fasted women (59.5 ± 5.8 years; BMI: 28.9 ± 3.9 kg·m −2 ) completed three isoenergetic cycling exercise sessions in a counterbalanced, randomized order: (a) MICE [35 minutes at 60%‐65% of peak heart rate, HRmax ], (b) HIIE 1 [60 × (8‐s cycling‐12‐s recovery) at 80%‐90% of HRmax ], and (c) HIIE 2 [10 × 1min at 80%‐90% of HRmax  − 1‐min recovery]. Then, VO2 and fat utilization measured at rest and during the 2 hours post‐exercise, enjoyment, perceived exertion, and appetite recorded during the session and energy intake (EI) and energy expenditure (EE) assessed over the next 24 hours were compared for the three modalities. Overall, fat utilization increased after exercise. No modality effect or time‐modality interaction was observed concerning VO2 and fat oxidation rate during the 2 hours post‐exercise. The two exercise modalities did not induce specific EI and EE adaptations, but perceived appetite scores at 1 hour post‐exercise were lower after HIIE 1 and HIIE 2 than MICE. Perceived exertion was higher during HIIE 1 and HIIE 2 than MICE, but enjoyment did not differ among modalities. The acute HIIE responses did not allow explaining the greater fat mass loss observed after regular high‐intensity interval training in post‐menopausal women with overweight/obesity. More studies are needed to understand the mechanisms involved in such adaptations.